EFEKTIVITAS PENGGUNAAN ASAM TRANEKSAMAT ORAL PADA PASIEN MELASMA - Al Mas - Nurissyita (LPPMK STIKES Widyagama Husada, 2021)
This study aims to determine the effectiveness of using oral tranexamic acid in melasma patients, as well as to explain the definition of melasma, melasma epidemiology, melasma etiopathogenesis, and to explain the effectiveness of using oral tranexamic acid in melasma. The method used was to collect and analyze research articles on the effectiveness of the use of oral tranexamic acid topical drugs in Melasma patients. The articles are obtained through a search using Google Scholar, Pubmed. The term melasma comes from the Greek word